Effect of Mango Leaf Meal as Supplementary Feed on Growth Parameters of Rohu (Labeo rohita) Fingerlings - , Komal Khatik, Rakhi Das, Deepak Kher, Shriparna Saxena (Archives of Current Research International, 2025)
The incorporation of different feed ingredients in fish diets contributes to protein sparing while improving palatability and energy utilization. The present study was conducted to evaluate the effect of mango leaf meal as supplementary feed on growth parameters of rohu (Labeo rohita) fingerlings at different inclusion levels. An experiment was conducted to evaluate the effect of mango leaf meal (MLM) as supplementary feed on growth parameters of rohu (Labeo rohita) fingerlings. Four different concentrations of MLM were incorporated into the basal diet at 2%, 4%, 8%, and 16% levels. The experiment was conducted for 60 days using a completely randomized design with triplicate treatments. Results showed that MLM supplementation significantly improved fish growth parameters while maintaining optimal water quality conditions across all treatments. The 8% MLM supplementation (T3) demonstrated superior performance with the highest weight gain (19.31±0.136 g), percentage weight gain (59.77±1.557%), specific growth rate (0.036±0.016), and best feed conversion ratio (2.92±0.071). Water quality parameters remained within acceptable ranges throughout the experimental period. Based on these findings, MLM supplementation at 8% in the basal diet is recommended for enhancing growth performance of rohu fingerlings. Future research should focus on field trials with different stocking densities and extended culture periods to validate these findings under commercial conditions. Additionally, studies on the economic feasibility and long-term effects of MLM supplementation would provide valuable insights for the aquaculture industry.